Analisis Tanah Dasar Pondasi terhadap Kestabilan di Desa Wonodadi Kulon Kabupaten Pacitan - Gede Satya; Aris Heri Andriawan; Ahmad Ridho'i (JPM17: Jurnal Pengabdian Masyarakat, 2014)
Abstract. Changes in land use is a major cause of flooding and landslides. The addition of a load on the slopes of the body by making residential buildings on the edge of a slope or at the top of the hill is risky landslide. From the results of soil testing in Wonodadi Kulon village Pacitan, the carrying capacity of the land base is capable of supporting the weight of the building, namely: QB = 0.217 kg / cm2 <Qall = 0285 kg / cm2 (still safe). In the case of the wall down (sinkhole), tilt and cracks in several buildings at the site of the settlement, not because of low soil bearing capacity but due to the implementation of a technical error, also prone to landslides because the ground with a slope of 15-40% converted into residential or housing and soil compaction is not done correctly. The land on the slope surface is directly used for the placement of the building foundation, in addition to causing land subsidence and landslides in the rain, as well as uneven load distribution and downs of the carrying capacity of the soil due to the influence of the body of water seepage in soil slope.Â Â Keywords: live, soil stability, carrying capacity.